PHILOSOPHICAL INVESTIGATION OF THE HUMAN HEART IN THE HISTORY OF EASTERN PHILOSOPHICAL THOUGHT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article analyzes the gradual development of philosophical views on the soul in Eastern philosophy. The article also describes the interpretation of the human soul in Eastern philosophical thought and the formation of philosophical anthropological views on man.